Pengaruh Permainan Tradisional Terhadap Minat Belajar Siswa di UPTD SD Negeri 128 Barru - Iyan, Iyan (Universtas Negeri Makassar, 2025)
The purpose of this study was to determine the influence of traditional games on students' interest in participating in physical education learning at the UPTD SD Negeri 128 Barru, Barru Regency. The method used in this study was a pre-experimental design with a one-group pretest-posttest. The study population included all students at the UPTD SD Negeri 128 Barru, while the sample was fifth-grade students. The data collection instrument used was a questionnaire. For data analysis, a paired sample t-test was used with a significance level of α <0.05. Based on the analysis, it was found that traditional games have a positive influence on students' interest in physical education, sports, and health learning at the UPTD SD Negeri 128 Barru.